Corrosion protection of AZ31 alloy and constrained bacterial adhesion mediated by a polymeric coating obtained from a phytocompound - Bertuola, Marcos (2018)
The prevention of microbial biofilm formation on a biomaterial surface is crucial in avoiding implants failures and the development of antibiotic resistant bacteria. It was reported that biodegradable Mg alloys may show antimicrobial effects due to the alkalinization of the corroding area. However, this issue is controversial and deserves a detailed study, since the processes occurring at the [biodegradable metal/biological medium] interface are complex and varied. Results showed that bacterial adhesion on AZ31 was lower than that of the titanium control and revealed that was dependent on surface composition, depicting some preferential sites for bacterial attachment (C-, P-, O-containing corrosion products) and others that are particularly avoided (active corrosion sites). As a key challenge, a strategy able to improve the performance of Mg alloys by both, reducing the formation of corrosion products and inhibiting bacterial adhesion was subsequently developed. A polymeric layer (polyTOH) was obtained by electropolymerization of thymol (TOH), a phytophenolic compound. The polyTOH can operate as a multifunctional film that improves the surface characteristics of the AZ31 Mg alloy by enhancing corrosion resistance (ions release was reduced to almost the half during the first days) and create an anti-adherent surface (bacterial attachment was 30-fold lower on polyTOH-AZ31 than on non-coated Mg alloy and 200-fold lower than Ti control and was constrained to specific regions). This anti-adherent property implies an additional advantage: enhancement of the efficacy of antibiotic treatments.